Lithuanian Children in Exile: Expeditions to Rescue Children - Briedienė, Ramunė (Genocidas ir rezistencija, 2025)
Illegitimacy of deportations of 1941 were understood even by some USSR leaders who initiated repatriation of orphans. The beginnings of rescue expeditions lies in the requests of relatives addressed to the Chairman of the Presidium of the USSR SS (Supreme Soviet) Justas Paleckis and some other influential persons. The lists of children to be repatriated were confirmed by the Chairman of the Presidium of the USSR SS Justas Paleckis or the Deputy Minister of Education Jonas Šalkauskas. There were also enlightened persons resolved to bring the children back: Marcelinas Ignatavičius, Petras Monstavičius, Jonas Bulota, Ona Jakubėnaitė, Zakarevičius and Kuznecova. They had to overcome different difficulties: problematic communication, unfavorable weather conditions, long formalities, determinant fights with exile authorities, many of whom did not regarded resolutions of the Presidium of the USSR SS. As a result of those obstructions, expeditions would last two or three months. Moreover, at any moment there was also a danger of the NKVD (MVD) roadblocks and examination of papers; some repatriations were organized illegally as well. Formally, there was a permission to repatriate only minors and complete orphans. However, the expedition leaders did not respect this order, their aim was to bring back as many Lithuanian children as possible. Therefore, they would fudge cases, birth dates and use other illegal ways to bring the children back. Thanks to the rescuers' resourcefulness, persistence and readiness to risk, twice as many children as it had been recommended were brought back to Lithuania.
Keywords: Soviet occupation; deportations; children; Gulag; rescue operations